Enhancing Social Tolerance and Community Participation through a Social-Educational Program in Pilowo Village - Sarapung, Risky Richlos; Jaguna, Fahmi; Sibua, Abd Sarman; Hayun, Subhan; Sibua, Amrin; Papingka, Gullyt Karlos; Mahmud, Nurhani; Sabban, Irawati; Lessy, Ledy Yanti (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
This Integrated Social and Educational-Based Program aimed to enhance community participation and social tolerance in Pilowo Village, South Morotai District, Pulau Morotai Regency. The program was initiated due to limited and sporadic community participation that had not been systematically integrated into village development initiatives. The implementation employed a participatory-collaborative approach through stages of socialization, collective community service activities, educational and recreational events, and a public dialogue session at the end of the program. Evaluation was conducted using mixed methods involving 78 respondents through pre-test and post-test questionnaires, interviews, and focus group discussions. The results indicated significant improvements in social participation (M=3.12 to 4.36), social tolerance (M=3.25 to 4.41), and awareness of education and community empowerment (M=3.05 to 4.28) with significance value p<0.001. Qualitative findings revealed strengthened social interaction, cross-group communication, and collective commitment toward program sustainability. The program demonstrates that a structured participatory approach effectively strengthens social capital and supports inclusive and sustainable village development.